DESAIN APLIKASI PENGENALAN POLA TANDA TANGAN MENGGUNAKAN METODE SUPPORT VECTOR MACHINE (SVM) - Gunawan, Gunawan; Reswan, Yuza (Jurnal Media Infotama, 2021)
The use of signatures is currently widely used to verify the validity of various financial transactions. Checks, credit cards and various other documents use signatures as identification of a person's legitimacy. Identification technology for recognition of signature patterns is included in biometrics which uses natural human behavioral characteristics. In this research, a signature pattern recognition application design will be created using the Support Vector Machine method. The goal to be achieved is to build a system that can detect types of signature forgery based on the Support Vector Machine method. The conclusion of this research makes it easier to recognize a person's signature pattern so that information on the owner of the signature can be known and obtain data about the signature pattern. The design of this application can help users in efforts to detect signatures. This design is suitable for use so that it can make it easy to recognize a person's signature pattern so that information about the owner of the signature can be known. The results of Matlab processing on image processing and artificial neural networks are usually stored in the *.mat extension because image processing and artificial neural network variables are numeric.